2022
DOI: 10.3390/d14050375
|View full text |Cite
|
Sign up to set email alerts
|

Study of Biodiversity of Algae and Cyanobacteria of Mutnovsky and Gorely Volcanoes Soils (Kamchatka Peninsula) Using a Polyphasic Approach

Abstract: Volcanic activity has a significant influence on the development of terrestrial ecosystems, including the Kamchatka Peninsula. We aimed to study the terrestrial algoflora of the Mutnovsky and Gorely volcanoes based on the use of clonal cultures of algae and cyanobacteria, and phenotypic and molecular genetic analyses. A total of 48 taxa were identified: 9 cyanobacteria, 32 Chlorophyta (11 Chlorophyceae, 21 Trebouxiophyceae), 3 Ochrophyta, and 4 Charophyta. In soils of the Mutnovsky volcano, 30 taxa were found,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
1
0
2
Order By: Relevance
“…Green algae species with different habitats are grouped into the same genus so that the two species are still closely related. According to Allaguvatova et al [24], Chlorococcum is a genus commonly found in terrestrial ecosystems. Chlorococcum hypnosporum is found in the forest steppes of Ukraine.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Green algae species with different habitats are grouped into the same genus so that the two species are still closely related. According to Allaguvatova et al [24], Chlorococcum is a genus commonly found in terrestrial ecosystems. Chlorococcum hypnosporum is found in the forest steppes of Ukraine.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…2021;Никулин и др. 2021;Allaguvatova et al 2022), среди которых лишь некоторые базировались на результатах идентификации комплексным подходом, эти виды отсутствовали. Наши находки являются новыми данными, которые вносят определенный вклад в биогеографию исследованных видов цианобактерий и водорослей.…”
Section: заключениеunclassified
“…Цианобактерии и микроскопические водоросли способны жить в крайне разнообразных и порой экстремальных местообитаниях: в соленой и пресной воде; на камнях и скалах; на вулканическом пепле и пирокластических отложениях; на коре деревьев; в почве и биологических почвенных корках; пещерах; снежных полях; горячих источниках и в оазисах пустынь (например, Mikhailyuk et al 2019;Abdullin et al 2021a;Saber et al 2021;Allaguvatova et al 2022). Эти микроорганизмы являются основными первичными производителями кислорода, органических соединений, основой пищевых цепей, ценными источниками биологически активных веществ для биотехнологических исследований и производств.…”
Section: Introductionunclassified